External Debt Crisis and Nigeria’s Economic Growth - Aguwamba; M., Sunday; Raph, Adeghe (International Journal For Research In Business, Management And Accounting, 2017)
This study examines the external debt crisis and Nigeria’s economic growth. It covers a period of 30 years (1979-2008) with GDP, external debt and external debt service payments as the variables. The GDP is the dependent variable, while external debt and external debt service payments are the independent variables. Cointegration econometric model is used for the estimation and the Unit root test is conducted in order to ascertain the stationarity of the variables. The results indicate that the GDP has positive relationship with the external debt and negative relationship with the external debt service payments. The cancellation of the Nigerian external debt by the Paris Club of creditors promises a great relief to the country. It was recommended that Nigeria should channel borrowed funds to profitable and designated activities. Further, external debt could be used to finance export generating projects of the country. Finally, corruption or embezzlement should be seriously fought against.